Efficient Proximity Coupled Feed Rectangular Microstrip Patch Antenna with Reduced Harmonic Radiation - Dawit Fistum (Institute of Advanced Engineering and Science, 2017)
This paper presents an efficient proximity coupled feed rectangular microstrip patch antenna with reduced harmonic radiation. The proposed antenna resonates in S-band at frequency of 2.45 GHz with bandwidth of 88.5 MHz. A very good return loss of -47.0546 dB is obtained for the Microstrip patch antenna. The antenna matching can be achieved with an appropriate line-patch overlap, but with a careful design consideration. Not only the good matching of the fundamental mode, but also the effect on the harmonic radiation from the other patch modes has been considered. Varying the length & location of the microstrip feed line and introducing a defect in the ground plane- the harmonic radiation from the other patch mode is reduced to minimum.